Cigarette smoking and the risk for cartilage loss and knee pain in men with knee osteoarthritis. Issue 1 (7th December 2006) - Amin, S; Niu, J; Guermazi, A; Grigoryan, M; Hunter, D J; Clancy, M; LaValley, M P; Genant, H K; Felson, D T
Abstract : Objective: To examine the effects of smoking on cartilage loss and pain at the knee in individuals with knee osteoarthritis. Methods: 159 men with symptomatic knee osteoarthritis who participated in a 30-month, prospective, natural history study of knee osteoarthritis were examined. The more symptomatic knee was imaged using magnetic resonance imaging (MRI) at baseline, and again at 15 and 30 months of follow-up. Cartilage was scored using the Whole-Organ MRI Score semiquantitative method at the medial and lateral tibiofemoral joints and at the patellofemoral joint. At baseline and follow-up visits, the severity of knee pain was assessed using a Visual Analogue Scale pain score (0–100 mm). Results: Among the 159 men, 19 (12%) were current smokers at baseline. Current smokers were younger (mean (standard deviation (SD)) age 62 (9) v 69 (9) years) and leaner (mean (SD) body mass index (BMI): 28.9 (3.2) v 31.3 (4.8) kg/m 2 ) than men who were not current smokers. When adjusted for age, BMI and baseline cartilage scores, men who were current smokers were found to have an increased risk for cartilage loss at the medial tibiofemoral joint (odds ratio (OR) 2.3, 95% confidence interval (CI) 1.0 to 5.4) and the patellofemoral joint (OR 2.5, 95% CI 1.1 to 5.7). Current smokers also had higher adjusted pain scores at baseline (60.5 v 45.0, p<0.05) and at follow-up (59.4 v 44.3, p<0.05) than men who were not current smokers. Conclusions: Men with knee osteoarthritis who smoke sustain greater cartilage loss and have more severe knee pain than men who do not smoke.